Sensorimotor Cortical Neuroplasticity in the Early Stage of Bell's Palsy. (19th February 2017) - Song, Wenwen; Dai, Minhui; Xuan, Lihua; Cao, Zhijian; Zhou, Sisi; Lang, Courtney; Lv, Kun; Xu, Maosheng; Kong, Jian
Abstract : Neuroplasticity is a common phenomenon in the human brain following nerve injury. It is defined as the brain's ability to reorganize by creating new neural pathways in order to adapt to change. Here, we use task-related and resting-state fMRI to investigate neuroplasticity in the primary sensory (S1) and motor cortex (M1) in patients with acute Bell's palsy (BP). We found that the period directly following the onset of BP (less than 14 days) is associated with significant decreases in regional homogeneity (ReHo), fractional amplitude of low frequency fluctuations (fALFF), and intrinsic connectivity contrast (ICC) values in the contralateral S1/M1 and in ReHo and ICC values in the ipsilateral S1/M1, compared to healthy controls. The regions with decreased ReHo, fALFF, and ICC values were in both the face and hand region of S1/M1 as indicated by resting-state fMRI but not task-related fMRI. Our results suggest that the early stages of BP are associated with functional neuroplasticity in both the face and hand regions of S1/M1 and that resting-state functional fMRI may be a sensitive tool to detect these early stages of plasticity in patient populations.